Automation of the Healthcare System in Iraq - AL-Zwaini, Isam (AL-Kindy College Medical Journal, 2024)
In the last few years, following the relative stability of the political, economic, and security environments, Iraq has embarked on a transformation towards an ambitious program of automation across various sectors. However, this automation program faces numerous challenges, including significant investments in technology and training, addressing social impacts, and combating widespread illiteracy